DA RAZÃO MONOLÍTICA À RAZÃO TRANSVERSAL. ITINERÁRIO DA FORMAÇÃO TEOLÓGICA ECUMÊNICA EM ABYA-YALA 1980-2000 - Alvarado, Jorge Almicar Ulloa (2010)
This is a research on the development of an ecumenical theological educational approach that came about in the framework of an organization of Protestant stamp. Since its origins there was a hint that this approach could be developed through the support of contextual theologies that were incipient at the time. This process covers a period of twenty years from 1980 to 2000, during which is possible to identify two major stages. The first one, under the name of Special Fund for Ecumenical Theological Education in Latin America (FEPETEAL), goes from 1980 to 1988. A plural movement limited to a Protestant scope was partially responsible for its creation. Although FEPETEAL really had the best intentions concerning its objective, it was entangled with the distribution of funds to prevent the closing of ecumenical seminaries. Furthermore, this stage was characterized by a certain ecumenical elitism , most masculinising traits. The second stage, an organic successor of the first one, was named Ecumenical Community of Theological Education in Latin America and the Caribbean (CETELA), between 1988 and 2000. This time, the impact of an ample and plural movement existent in several newer and also in some older theological institutions, transformed the organization until the point to create the New CETELA in 1993, a community in which can be found several theological thoughts committed to the claims of sectors marginalized of Abya-Yala, for ethnic, cultural, social, religious, and gender reasons. Originated from pluricultural perspectives, this movement was part of the processes that withstood the single thought of non-liberal logic. A new ecumenical proposal sprang from the interface of those emergent sectors, the old representatives of LT, and the need of the theological institutions to have an educational offer incarnated in the diversity of the region. Is the result of a theological/pedagogical task that adopted transversability as a hermeneutic tool that allows the intersubjective transformation among different knowledge .